IMPROVEMENT OF CRITICAL THINKING ABILITY IN BASE ACID MATERIAL THROUGH THE APPLICATION OF EDMODO-BASED DISCOVERY LEARNING MODEL - Cola, Nova; Nuswowati, Murbangun (JTK (Jurnal Tadris Kimiya), 2020)
This study aimed to determine the improvement of students’ critical thinking abilities through the application of edmodo’s assisted discovery learning model. The study was conducted on students of class XI MIPA 2 high school 2018/2019. This study used a true experimental design in the form of a pre-test and post-test control group design. Sampling was done by a cluster random sampling technique. Data collection used reasoned multiple choice test instruments and questionnaires. The result of test analysis of students’ critical thinking skills showed that the average post-test value of the experimental class was lower than the control class. The N-gain test result showed that the magnitude of the increasing of the experimental class was 0.43 lower than the control class which is equal to 0.57. The application of edmodo assisted discovery learning model had a positive effect on students’ critical thinking abilities with a low category as indicated by the correlation coefficient of 0.37 and the magnitude of the influence given is 14.08%. The conclusion of this study is the application of edmodo assisted discovery learning model can improve students’ critical thinking skills. Furthermore, students agree to use edmodo’s assisted discovery learning model for acid base learning.